Use of citation analysis to predict the outcome of the 2001 Research Assessment Exercise for Unit of Assessment (UoA) 61: Library and Information Management - Alison Holmes; Charles Oppenheim (Information Research: An International Electronic Journal)
A citation study was carried out to predict the outcome of the 2001 Research Assessment Exercise. The correlation between scores achieved by academic departments in the UK in the 1996 Research Assessment Exercise, and the number of citations received by academics in those departments for articles published in the period 1994-2000, using the Institute for Scientific Information’s citation databases, was assessed. A citation study was carried out on all three hundred and thirty eight academics that teach in the UK library and information science schools. These authors between them received two thousand three hundred and one citations for articles they had published between 1994 and the present. The results were ranked by Department, and compared to the ratings awarded to the departments in the 1996 Higher Education Funding Council Research Assessment Exercise. On the assumption that RAE scores and citation counts are correlated, predictions were made for the likely RAE scores in the 2001 RAE. Comments were also made on the impact of staff movements from one Higher Education Institution to another.